Sita Marital Harta Bersama Dalam Perkara Perceraian di Pengadilan Agama - risdianti bonok (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
The process of resolving marital seizure applications on joint assets in a divorce case at the Religious Court is carried out with stages starting from the application of the marital seizure to objects, both movable and immovable goods. It is highly dependent on concrete and demonstrable reasons regarding seizure placement in trial face. If the seizure request can be granted by the panel of judges according to strong evidence and proven in the trial, the panel of judges can conduct marital seizure by ordering the registrar to be assisted by the bailiff to confiscate movable or immovable items to be recorded. Marital seizure contained in the object of the dispute in the contents of the claim with the local government present. Whereas judicial legal considerations regarding marital seizure applications, the panel of judges, firstly looks at the facts from the trial. If the seizure is granted then enough reason for seizure applicants to be placed marital seizure. And if the seizure application is rejected and there is no enough reason to place the marital seizure by the panel of judges because there was no concern, the defendant will move or transfer the object of the dispute to another person who was carried out through a hearing outside the Religious Court which is also called the local hearing